Trading binary options : strategies and tactics - Cofnas, Abe, 1950- (Bloomberg financial series., 2012)
"An essential guide to the fast growing area of binary optionsLong the province of professional traders, binary options are now offered to retail investors through the North American Derivative Exchange (Nadex) and a growing group of online brokerages. Now, with this new book, author Abe Cofnas explains how independent traders and investors can use binary options to speculate on price movements and global events. The great appeal of binary options is that they are less complex than conventional options and provide a simple method to trade based on an opinion of where the market is headed over a certain period of time. Engaging and informative, this reliable guide reveals how binary options work, what are the best binary options trading strategies, and when to use them. Identifies the various markets in which binaries are available Offers insights on how binary options allow for opportunities to speculate on the direction of a market and receive a substantial payout Provides suggestions as to which markets provide the best liquidity and lowest trade execution expenses As the first book solely devoted to this topic, Binary Options will provide retail traders with an authoritative guide to trading this exciting new market"--Provided by publisher.